(untitled) (Health Renaissance, 2011)
Introduction: A hemangiopericytoma is a rare, soft-tissue tumor of vascular origin derived from a pericyte of Zimmerman, which is a modified smooth muscle cell that surrounds the small blood vessels. Hemangiopericytomas can occur wherever there are vascular capillaries. However, there were no previous reports of a hemangiopericytoma in the retroperitoneal space. Case presentation: We describe the first reported case of a hemangiopericytoma found in the retroperitoneal space. A 25-year-old man presented with a palpable tumor on the left abdomen. Preoperative imaging indicated that the tumor was in the retroperitoneal space without invasion of other organs. A complete resection was performed via a midline incision. The histological and immunohistochemical staining patterns supported the diagnosis of a hemangiopericytoma. Conclusion: A complete resection without piecemeal excision is the best way to treat a hemangiopericytoma. Recognizing the presence of a hemangiopericytoma in the retroperitoneal space requires appropriate surgery. DOI: http://dx.doi.org/10.3126/hren.v9i3.5593 HR 2011; 9(3): 210-213